Less Vertebral Bone Mass after Treatment with Macitentan in Mice: A Pilot Study. - Liu, Zhong-Yu; Au, Man-Ting; He, Tian-Wei; Yang, Bu; Liu, Bin; Zhang, Liang-Ming; Luo, Chun-Xiao; Rong, Li-Min; Wen, Chun-Yi (BioMed Research International, 2019)
Purpose. Blood vessels and skeleton interact together. Endothelin-1 is a potent vasoconstrictor and also has an effect on bone metabolism. The dual antagonist to both endothelin-1 type A and B receptors, Macitentan, has been approved for clinical management of pulmonary arterial hypertension while little is known about the secondary effect of the drug on spine. We aimed to answer how vertebral bone mass responded to Macitentan treatment in mice. Methods. Sixteen male balb/c mice at 6 months were randomly assigned into 2 groups. Vehicle and Macitentan were administrated via intraperitoneal injection to Control group and Treatment group, respectively, for 4 months. At sacrifice, plasma endothelin-1 was evaluated with ELISA and vertebral bone mass was evaluated with Microcomputed Tomography and histological analysis. Results. We found higher plasma endothelin-1 level (p<0.01) and less vertebral bone mass (p<0.05) in Treatment group compared to controls. Moreover, less osteoblasts and more osteoclasts were observed in the vertebral trabecular bone in the Treatment group compared to controls, by immunohistochemistry of the cell-specific markers. Conclusions. Treatment with Macitentan is associated with significant lower vertebral bone mass and therefore the secondary effect of dual antagonists to endothelin-1 receptors on the skeleton should be monitored and investigated in clinical practice. Both osteoblasts and osteoclasts may be involved while the molecular mechanism needs to be further explored.